SAT0252 INCREASED MORTALITY FOR INDIVIDUALS WITH GIANT CELL ARTERITIS: A POPULATION-BASED STUDY. (2nd June 2020) - Barra, L.; Pope, J.; Pequeno, P.; Gatley, J.; Widdifield, J.
Abstract : Background: Individuals with giant cell arteritis (GCA) are at increased risk of serious morbidity including cardiovascular disease and stroke. Yet the risk of mortality among individuals with GCA have produced conflicting reports 1 . Objectives: Our aim was to evaluate excess all-cause mortality among individuals with GCA relative to the general population over time. Methods: We performed a population-based study in Ontario, Canada, using health administrative data among all individuals 50 years and older. Individuals with GCA were identified using a validated case definition (81% PPV, 100% specificity). All Ontario residents aged 50 and above who do not have GCA served as the General Population comparators. Deaths occurring in each cohort each year were ascertained from vital statistics. Annual crude and age/sex standardized all-cause mortality rates were determined for individuals with and without GCA between 2000 and 2018. Standardized mortality ratios (SMRs) were calculated to measure relative excess mortality over time. Differences in mortality between sexes and ages were also evaluated. Results: Population denominators among individuals 50 years and older with GCA and the General Population increased over time with 12, 792 GCA patients and 5, 456, 966 comparators by 2018. Annual standardized mortality rates among the comparators steadily declined over time and were significantly lower than GCA morality rates (Figure). Annual GCA mortality rates fluctuated between 42-61 deaths per 1000 population (with overlapping confidence intervals) during the same time period. SMRs for GCA ranged from 1.28 (95% CI 1.08, 1.47) at the lowest in 2002 to 1.96 (95% CI 1.84, 2.07) at the highest in 2018. GCA mortality rates and SMRs were highest among males and younger age groups. Conclusion: Over a 19-year period, mortality has remained increased among GCA patients relative to the general population. GCA mortality rates were higher among males and more premature deaths were occurring at younger age groups. In our study, improvements to the relative excess mortality for GCA patients over time (mortality gap) did not occur. Understanding cause-specific mortality and other factors are necessary to inform contributors to premature mortality among GCA patients. References: [1]Hill CL, et al. Risk of mortality in patients with giant cell arteritis: a systematic review and meta-analysis. Semin Arthritis Rheum. 2017;46(4):513-9. Acknowledgments: This study was supported by a CIORA grant Disclosure of Interests: Lillian Barra: None declared, Janet Pope Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly & Company, Merck, Roche, Seattle Genetics, UCB, Consultant of: AbbVie, Actelion, Amgen, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Eicos Sciences, Eli Lilly & Company, Emerald, Gilead Sciences, Inc., Janssen, Merck, Novartis, Pfizer, Roche, Sandoz, Sanofi, UCB, Speakers bureau: UCB, Priscila Pequeno: None declared, Jodi Gatley: None declared, Jessica Widdifield: None declared